The Influence of Brand Image and Online Customer Reviews Against Purchasing Decisions on the Marketplace Lazada - Oktaviani, Winda; Suhardi, Dadang; Kusumawati, Indah Dwi; Seliana, Dila (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aimed to determine: (1) The influence of brand image on purchasing decisions. (2) The influence of online customer reviews on purchasing decisions. (3) brand image and online customer reviews influence purchasing decisions. The method used is a quantitative method using descriptive analysis. The population in this study are Lazada users in Kuningan Regency whose number is unknown. Sampling used the Lemeshow formula with a total sample of 100 respondents. The sampling technique is nonprobability sampling using a purposive sampling method. The data collection technique used in this study was distributing questionnaires and measuring them using an interval scale. Data analysis used multiple linear regression analysis assisted by IBM SPSS version 23 software. Based on the results of the research that has been done, it shows that (1) Brand image has a positive and significant influence on purchasing decisions. (2) Online customer review has a positive and significant influence on purchasing decisions. (3) Brand image and online customer reviews simultaneously have a positive and significant influence on purchasing decisions.